STATUS KEWARGANEGARAAN ANAK YANG LAHIR DARI PERKAWINAN BEDA KEWARGANEGARAAN (TELAAH WACANA GLORIA NATAPRADJA HAMEL) - Asia, Nur (Universitas Tadulako, 2019)
ABSTRACTâ€œThe Citizenship Status of Chilldren who Born from Marriage Differet Nationality (Discourses Review of Gloria Natapradja Hamel)â€, The problem of thisÂ research is (1) How is the consequence of Legal Status of Indonesia Citizenship over the case of Gloria Natapradja Hamel? (2) How is the legal protection of citizenship status of children who born fromÂ marriage different nationality? The research method used was normative legal research method with the approac of legislation, conseptual and case approaches. The research results show that (1) the phenomenon of citizenship status of Gloria Natapradja Hamel is not clear. (2) The Acts Number 12 of 2006 about citizenship does not provide legal protection on citizenship status of children who born from marriage different nationality.Â Keywords: Marriage Different Nationality, Citizenship Â